Ingestão de fluoreto e risco de fluorose dentária - Santos, Cristiane Brandão (2017)
Introduction: Dental fluorosis is an alteration in dental enamel mineralization, related to fluoride (F־) intake. Objectives: To investigate the impact of F־ addition in toothpaste on the prevalence of dental fluorosis and to compare methods for F־ determination in samples of diet and toothpaste. Methods: Two studies were developed: 1) systematic review of the literature, with meta-analysis, performed by two reviewers independently searching the four electronic databases (MEDLINE / PubMed; MEDLINE / Ovid; Bireme and Web of Science). The quality of articles eligible for Strengthening the Reporting of Observational Studies in Epidemiology (STROBE), and by the classification modified by Irani (2013); 2) a laboratory study that determined the F־ concentration in the diet and dentifrice samples using two extraction methods: HMDS facilitated microdiffusion and hydrolysis in 0.01M HCl at times 30, 60 and 120 min of incubation. For analysis of the data, the one-way ANOVA test was applied. Results: 1) In the systematic review, eleven articles were eligible, and, when STROBE was applied, the number of items included ranged from 14 and 19, with an average of 16.3 and a standard deviation of 4.03; in the analysis of the classification modified by Irani (2013), two articles were classified as high quality and the rest of intermediate quality; 2) the method of extraction using 0.01M HCl, in the time 30 min, resulted in similar values to that expected by inactivation of 50% of the dentifrice’s F־. And in time 120 min resulted in similar values to HMDS facilitated microdiffusion. Conclusion: The majority of eligible articles in the systematic review found an association between the age of fluoride toothpaste use and dental fluorosis, but the prevalent severity of fluorosis was very mild, ie it does not imply dental fluorosis as a public health problem. It's the method of F־ extraction using 0.01M HCl, in the experimental study, was promising to be used in evaluation of F־ in dietary intake and dentifrices.